Validity of digital periapical radiography and cone beam computed tomography in the detection of peri-implant bone defects: in vitro study - Elera Morales, César C. (2023)
Abstract: To compare the diagnostic accuracy of digital radiography (DR) and cone beam computed tomography (CBCT) in the detection of peri-implant bone defects. Materials and methods: Implants were placed in 5 fresh bovine ribs (3 without peri-implant bone defects, 12 with 1.4mm peri-implant bone defects) and images were taken using (i) portable x-ray system (DEXCOWIN 3000), (ii) intraoral x-ray sensor (SENSOR H1/SENSOR H2), (iii) volume-limited HSCT with 3D Accuitomo 80 (CASTELLINI). Images of each were randomly presented to 10 examiners. Confidence in the diagnosis of the presence or absence of a peri-implant radiolucency was recorded on a scale of bone defect definitely absent, doubts about the defect if absent or present, defect definitely present. Analyzes was performed using a kappa test. Results: There has been a coincidence between the direct digital radiography and the cone beam computed tomography in piece A of 83.3%, in piece B of 100% and in piece C of 88%, giving an average total coincidence 90.43%. Conclusion: Direct digital radiography provides the same results as cone beam computed tomography in the detection of peri-implant bone defects at an early stage. Digital radiographs are a reliable and valid method and perform significantly better than cone beam computed tomography for detecting peri-implant bone defects at an early stage.